Accelerating Graphical DSL Development: Live Metamodeling in Cinco Cloud - Mitwalli, Daniel Sami (Electronic Communications of the EASST, 2025)
Language engineering of graphical Domain-Specific Languages (DSLs) often involves inefficient repetitive compilations when using a generative approach for corresponding Integrated Modeling Environments (IMEs). Instead of generating and compiling dedicated IMEs for each language, this work proposes using a general-purpose IME to interpret the syntax and semantics of graphical DSLs. This approach eliminates the compilation time of dedicated IMEs and serves as a platform that streamlines the language engineering process, enabling real-time adjustments and direct use of the resulting graphical DSL.